Approximations to the Distribution Functions of the Ordinary Least Squares and Two-Stage Least Squares Estimators in the Case of Two Included Endogenous Variables - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 1973)
This paper deals with single-equation estimators in a simultaneous system of linear stochastic equations and approximates the distribution function of the two-stage least-squares estimators up to terms whose order of magnitude is $1/\sqrt{N}$, where N is the sample size. For fixed N, an approximation to the OLS distribution function is also obtained up to terms whose order of magnitude 1/Î¼, where Î¼ 2 is what is referred to in the literature as the concentration parameter.